Postmodern malpractice a medical case study in the culture war - Clements, Colleen D. (Advances in bioethics ;, 2001)
In this work, Colleen Clements presents her case for the need to subject the field of bioethics to a critical external analysis apart from the current postmodern assumptions. Clements argues that, since the 1970s, bioethics has refuted human values in favour of political consensus building. This failure to recognize basic human values in the ethical critique of modern medicine has lead to a dehumanization of the medical system by the field. Clements proceeds to advocate a naturalistic theory of bioethics that reinstates primary human values.